1967
DOI: 10.1002/aic.690130312
|View full text |Cite
|
Sign up to set email alerts
|

Influence of resin selectivity on film diffusion‐controlled ion exchange

Abstract: An analytic solution of the Nernst‐Planck equations is derived which applies to a selective resin when film diffusion controls. The selectivity has a marked effect on the rate of exchange for a wide range of diffusivities. The unit‐selectivity solution of Schlögl and Helfferich is included as a special case of the more general solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1969
1969
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…There exists a large number of studies of the liquid-side mass transfer in a binary ion exchange system. The mathematical descriptions for such a system have been presented by many investigators (Copeland et al, 1967;Copeland and Marchellow, 1969;Glasski and Dranoff, 1963;Kataoka et al, 1968Kataoka et al, , 1971Kataoka et al, , 1973Schlogle and Helfferich, 1957;Smith and Dranoff, 1964;Turner and Snowdon, 1968a, b). Schlogle and Helfferich (1957) first applied the Nernst-Planck (N-P) equation to the fluxes of ionic species and showed that the electric field caused by the difference in the diffusivities affects the ion exchange rate significantly.…”
Section: Introductionmentioning
confidence: 99%
“…There exists a large number of studies of the liquid-side mass transfer in a binary ion exchange system. The mathematical descriptions for such a system have been presented by many investigators (Copeland et al, 1967;Copeland and Marchellow, 1969;Glasski and Dranoff, 1963;Kataoka et al, 1968Kataoka et al, , 1971Kataoka et al, , 1973Schlogle and Helfferich, 1957;Smith and Dranoff, 1964;Turner and Snowdon, 1968a, b). Schlogle and Helfferich (1957) first applied the Nernst-Planck (N-P) equation to the fluxes of ionic species and showed that the electric field caused by the difference in the diffusivities affects the ion exchange rate significantly.…”
Section: Introductionmentioning
confidence: 99%
“…They inspected the variables that influence the breakthrough of mixed-bed, and developed an empirical relationship between leakage and capacity. Kunin (1960) 5 Many researchers have performed numerous studies focused on liquid-side mass transfer in binary ion exchange systems; Copeland et al (1967) further conducted an experimental study on the kinetics of mixed-bed deionization. He examined the effects of influent concentration, flow rate, bed depth, and temperature on bed performance and concluded that the ion exchange rate was controlled by a liquid-film mass transfer mechanism at low concentrations.…”
Section: Mbie-sim Backgroundmentioning
confidence: 99%